The effect of the addition combination of chicken eggshell adsorbents (Gallus gallus domesticus) and siwalan fiber (Borassus flabellifer) on the adsorption process of used cooking oil - Siswanto, Anggun Puspitarini; Khasanah, Siti Khofifatul (Departemen Teknik Kimia Fakultas Teknik Universitas Gadjah Mada, 2023)
Cooking oil is a daily necessity. Repeated use of oil with high heating temperatures (200-250°C) can result in oxidation and polymerization processes in the oil. Cooking oil purification is carried out by the adsorption method which utilizes cellulose content in coconut coir and CaCO3 in eggshell so that it can meet SNI 3741:2013. In this study, the adsorption process was carried out using siwalan coir adsorbents activated by 9% ZnCl2 and eggshell adsorbents which were activated using a 600oC furnace for 3 hours. This study was handled using a factorial 23 experimental design and it was found that the adsorption spin time variable was the influential variable. The results of this study were per SNI 3741:2013 with an FFA concentration of 0.3049% and a peroxide value of 2 mekO2/kg with a mass of adsorbent for siwalan coir and shells of 2: 10 gram, the optimum time was 69 minutes. Analysis of the findings of the optimization sample which has a specific gravity of 0.91 gram/cm3, a clear yellow color, and a moisture content of 0.083%.